MENINGKATKAN KETERAMPILAN MEMBUAT PALAI BILIH MELALUI METODE DEMONSTRASI PADA ANAK TUNARUNGU KELAS D.V DI SDLB N 20 NANBALIMO) - Wartini - (Universitas Negeri Padang, 2015)
Abstract. The purpose of this research are:1) Improve the implementation of the process of learning the skills to make palai bilih through demonstration method for deaf children in the DV class SDLB No. 20 Nan Balimo Solok. 2) Prove that the method can improve the skills demonstration make palai bilih DV class of deaf children in SDLB No. 20 Nan Balimo Solok. This type of research is classroom action research, conducted in the form of collaboration with colleagues. Subject three children with hearing impairment DV class and one teacher. Data obtained through observation, testing. Then analyzed qualitatively and quantitatively. The results showed that 1) the learning process makes palai bilih using the demonstration carried out by two cycles. Cycle I and II with four meetings. Each cycle begins with the planning, implementation (initial activities, core and end), observation, analysis and reflection. 2) The results of the study by using demonstration method in making palai bilih increased. It can be seen from the data before the action children's ability to perform 18 steps to make palai bilih namely: SI (38.9%), RA is a (47.2%) and BP (52.8%). Whereas at the end of the first cycle SI capability increased to (66.7%) and RA (69.4%) and TD (75%). After the second cycle SI capability increased to (94.4%) and RA (97.2%) and TD became (100%). It can be concluded that these three children have increased ability to make Palai bilih after being given intensive method of demonstration to the class of deaf children in SDLB DV 20 Nanbalimo Solok. It is suggested to teachers the skills to be able to use the demonstration method in teaching other skills. Kata kunci: Palai Bilih; Metode Demonstrasi; Anak Tunagrahita Ringan